PATH-16. HISTOPATHOLOGICAL EPENDYMOMA VARIANTS ARE ASSOCIATED WITH DISTINCT CLINICAL PARAMETERS AND DNA METHYLATION PATTERNS. (11th November 2019) - Neumann, Julia E; Spohn, Michael; Obrecht, Denise; Mynarek, Martin; Thomas, Christian; Hasselblatt, Martin; Dorostkar, Mario M; Wefers, Annika K; Frank, Stephan; Monoranu, Camelia-Maria; Koch, Arend; Witt, Hendrik; et al.
Abstract: According to the current WHO classification, ependymal tumors are classified as subependymomas, myxopapillary ependymomas, classic ependymomas, anaplastic ependymomas and RELA -fusion positive ependymoma (RELA-EPN). Among classic ependymomas, the WHO defines rare histological variants, i.e. the clear-cell, papillary, and tanycytic ependymoma. In parallel to this WHO classification scheme, DNA methylation patterns can distinguish nine distinct molecular ependymoma subgroups, some of which tightly overlap with certain histopathological subgroups, e.g. subependyomas or myxopapillary ependymomas. Since very little is known about the molecular background of histological classic ependymoma variants, we analyzed histomorphology, clinical parameters and global DNA methylation patterns of diagnosed tanycytic ependymomas (n=12), clear-cell ependymomas (n=14) and papillary ependymomas (n=19). Surprisingly, up to 42% of these variants did not match to ependymomas using a previously published DNA methylation-based classifier for brain tumors. Among the tumors with a match to one of the nine known ependymoma methylation classes, tanycytic ependymomas were predominantly located in the spine, but showed diverse molecular methylation patterns. Most clear-cell ependymomas showed a common histomorphology, were found supratentorially and fell into the methylation class of RELA-EPN. Papillary ependymomas showed a "papillary", "trabecular" or "pseudo-papillary" growth pattern. Interestingly, a true papillary growth pattern was strongly associated with the molecular class B of posterior fossa ependymoma (PFB), but tumors displayed DNA methylation sites that were significantly different when compared to PFB ependymomas without papillary growth. Our results show that the diagnosis of classic histological ependymoma variants can be challenging. While clear-cell and papillary ependymomas harbor common molecular features, tanycytic ependymoma may not represent a molecularly distinct subgroup.